2021
DOI: 10.3390/nu13051491
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress at Birth Is Associated with the Concentration of Iron and Copper in Maternal Serum

Abstract: Oxidative stress (OS) in the foetal and neonatal periods leads to many disorders in newborns and in later life. The nutritional status of pregnant women is considered to be one of the key factors that triggers OS. We investigated the relationship between the concentration of selected mineral elements in the blood of pregnant women and the concentration of 3′nitrotyrosine (3′NT) as a marker of OS in the umbilical cord blood of newborns. The study group consisted of 57 pregnant women and their newborn children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 101 publications
(151 reference statements)
0
7
0
Order By: Relevance
“…The precise relationship between Cu and OS levels is not yet fully understood. A recent study by Rak et al [124] revealed a negative correlation between OS levels in male newborns and the concentration of Cu in maternal serum, which suggests a potential influence of Cu on OS during pregnancy, emphasizing the need for further research in this area.…”
Section: Coppermentioning
confidence: 99%
See 1 more Smart Citation

Oxidative Stress in Pregnancy

Grzeszczak,
Łanocha-Arendarczyk,
Malinowski
et al. 2023
Biomolecules
“…The precise relationship between Cu and OS levels is not yet fully understood. A recent study by Rak et al [124] revealed a negative correlation between OS levels in male newborns and the concentration of Cu in maternal serum, which suggests a potential influence of Cu on OS during pregnancy, emphasizing the need for further research in this area.…”
Section: Coppermentioning
confidence: 99%
“…In pregnant women without Fe deficiency anemia (IDA), prophylactic Fe supplementation has been shown to induce OS and compromise the overall antioxidant capacity of the body [124,131]. Specifically, Rak et al [124] established a correlation between excessive Fe concentrations exceeding 400 µg/dL in the blood of pregnant women and elevated levels of OS in neonates.…”
Section: Ironmentioning
confidence: 99%

Oxidative Stress in Pregnancy

Grzeszczak,
Łanocha-Arendarczyk,
Malinowski
et al. 2023
Biomolecules
“…The procedure for obtaining and storing MS samples was the same as for the UCS. The method of determining the concentration of macro-(Ca, Mg) and microelements (Zn, Fe, Cu) in the MS has been described in detail previously [44]. The concentrations of examined macro-and microelements in the MS were categorized based on reference values for women in the 3rd trimester of pregnancy (Table 2) [45].…”
Section: Determination In Maternal Serum Of Selected Macro-and Microe...mentioning
confidence: 99%
“…The research has indicated that excess Fe saturation during the prenatal period may elevate the risks of miscarriage, premature birth, low birth weight, and being small for gestational age (SGA), with OS being one of the likely mechanisms behind these abnormalities. In pregnant women without Fe deficiency anemia (IDA), prophylactic Fe supplementation has been observed to trigger oxidative stress and limit the organism's antioxidant capacity [30,31].…”
Section: Introductionmentioning
confidence: 99%